Gender Earnings Gaps in the Caribbean: Evidence from Barbados and Jamaica - Annelle Bellony; Alejandro Hoyos; Hugo Nopo (Inter-American Development Bank (IDB), 2010)
This paper analyzes gender earnings gaps in Barbados and Jamaica, using a matching comparisons approach. In both countries, as in most of the Caribbean region, females educational achievement is higher than that of males. Nonetheless, males earnings surpass those of their female peers. Depending on the set of control characteristics, males earnings surpass those of females by between 14 and 27 percent of average females wages in Barbados, and between 8 and 17 percent of average females wages in Jamaica. In the former, the highest earnings gaps are found among low-income workers. Results from both countries confirm a finding that has been recurrent with this matching approach: the complete elimination of gender occupational segregation in labor markets would increase rather than reduce gender earnings gaps. The evidence is mixed regarding segregation by economic sectors. Occupational experience, in the case of Barbados, and job tenure, in the case of Jamaica, help to explain existing gender earnings gaps.
Keywords: C14; D31; J16; O54; 330; Gender; Ethnicity; Wage gaps; the Caribbean; Barbados; Jamaica; Matching